Phylogenetic relationships of Elateridae inferred from adult morphology, with special reference to the position of Cardiophorinae - Douglas, Hume (Zootaxa, 2011)
A phylogeny is presented for the Elateridae, inferred from parsimony and Bayesian analyses of 175 adult morphological characters. Analyses using non gap-weighted morphological data yielded results compatible with each other and some published classifications, while gap-weighted parsimony analysis did not. Bayesian posterior probabilities for the monophyly of the Elateridae and the elaterid subfamilies Athoinae (sensu Dolin 1975), Cardiophorinae (including Exoeolus Broun), Denticollinae (sensu Stibick 1979a), Elaterinae (sensu Stibick 1979a), Hypnoidinae (sensu Stibick 1976) and Lissominae (sensu Calder et al. 1993) were less than 0.05. The bioluminescent genus Pyrophorus was found to be an apical member of the mostly non-bioluminescent Agrypninae, supporting the hypothesis of at least one independent origin of bioluminescence in the Elateridae. The closest relatives to the Cardiophorinae minus Exoeolus were found in the Negastriinae. The subfamilies Cardiophorinae + Negastriinae + Tropihypnus Reitter together rendered the Hypnoidinae (or the tribe Hypnoidini of Denticollinae) paraphyletic. Lesnelater madagascariensis Fleutiaux (the type species of Lesnelater Fleutiaux) is synonymised under the type species of Pachyelater Lesne: P. madagascariensis (Lesne) so that Lesnelater is a new synonym of Pachyelater. The genus Exoeolus Broun is transferred from the Cardiophorinae to the Hemiopinae; the fossil genus Crioraphes Iablokoff-Khnzorian is transferred to the Elaterinae incertae sedis; the fossil genera Pseudocardiophorites Dolin, and Protocardiophorus Dolin are transferred to Elateroidea incertae sedis. Dolin’s (1976) hypothesis of a Jurassic origin of the Cardiophorinae was not supported by fossil evidence.